Cortical actin nanodynamics determines nitric oxide release in vascular endothelium. - Johannes Fels (Public Library of Science (PLoS), 2012)
The release of the main vasodilator nitric oxide (NO) by the endothelial NO synthase (eNOS) is a hallmark of endothelial function. We aim at elucidating the underlying mechanism how eNOS activity depends on cortical stiffness (К(cortex)) of living endothelial cells. It is hypothesized that cortical actin dynamics determines К(cortex) and directly influences eNOS activity. By combined atomic force microscopy and fluorescence imaging we generated mechanical and optical sections of single living cells. This approach allows the discrimination between К(cortex) and bulk cell stiffness (К(bulk)) and, additionally, the simultaneous analysis of submembranous actin web dynamics. We show that К(cortex) softens when cortical F-actin depolymerizes and that this shift from a gel-like stiff cortex to a soft G-actin rich layer, triggers the stiffness-sensitive eNOS activity. The results implicate that stiffness changes in the ∼100 nm phase of the submembranous actin web, without affecting К(bulk), regulate NO release and thus determines endothelial function.